Strategies and obstacles for marketing innovation activities. (6th March 2019) - Correia, Aldina; Braga, Vitor; Machado, Ana; Braga, Alexandra
The recognised importance of innovation and their role in competitiveness of firms is well-known. Marketing innovation is one aspect of the general innovation process and, as such, deserves to be explored. Based on a sample of 6, 840 Portuguese firms which replied the 2012 Community Innovation Survey, multivariate techniques (factor analysis and multivariate linear regression) have been used to measure the factors associated with main strategies and obstacles of marketing innovation, in order to better understand the role of marketing in firms' innovation processes. Our results suggest that the majority of Portuguese firms display a limited marketing innovation strategy, with some focusing on innovation in design or packaging, product promotion, placement and pricing. Five factors were found associated with main motivations and obstacles for innovation processes: costs; improvement of goods or services and cooperation; internationalisation; market-related motivations; and financial issues. In addition, our results also suggest that marketing innovation is, mostly, explained by one of the firms 'motivations: the improvement of goods or services and cooperation.